Applying Accounting Records and Digital Marketing Increase SME’s Profits - Ayu Permata Sari; Laylan Syafina (University of Merdeka Malang, 2023)
This study aims to test whether the applying accounting records and digital marketing have an effect on increasing profits in SME’s in Deli Serdang Regency. This research is quantitative descriptive. The data collection process was carried out by distributing questionnaires and interviewing respondents. The population in this study were SME’s registered at the Cooperatives and SMEs Office of Deli Serdang Regency. Purposive sampling techique was used in determining the sample so that a sample of 50 SME’s that met the criteria which has applied accounting records and digital marketing. To process the data collected through distributing questionnaires, multiple linear regression testing was used. According to research findings, there is a positive and significant effect of applying accounting records and digital marketing on increasing profits in SMEs.